2013
DOI: 10.1111/tri.12155
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus trough levels after month 3 as a predictor of acute rejection following kidney transplantation: a lesson learned from DeKAF Genomics

Abstract: Most calcineurin inhibitor (CNI) based protocols reduce blood trough goals approximately 2–3 months post-transplant in clinically stable kidney transplant recipients. The CNI target trough level to prevent rejection, after reduction, is unknown. Using a multivariate Cox proportional hazards model we determined the association of time-varying tacrolimus (TAC) trough levels with acute rejection (AR) occurring in the first 6 months post-transplant, but specifically we assessed this association after 3 months. 1,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 26 publications
3
41
2
Order By: Relevance
“…They demonstrated in a multivariate analysis that low mean Tac exposure was independently associated with higher increase in biopsy‐proven chronicity scores [calculated as the sum of the four basic “chronic” Banff qualifiers (chronic glomerular damage, interstitial fibrosis, tubular atrophy, and vascular intimal thickening)] between 3 and 12 months after the transplantation. Recently, in the DeKAF study, a lower Tac exposure after month 3 was also associated with an increased risk of acute rejection . The association between the Tac IPV and poor kidney transplantation outcome was not significantly modified within four patients subgroups based on their mean Tac C 0 .…”
Section: Discussionmentioning
confidence: 89%
“…They demonstrated in a multivariate analysis that low mean Tac exposure was independently associated with higher increase in biopsy‐proven chronicity scores [calculated as the sum of the four basic “chronic” Banff qualifiers (chronic glomerular damage, interstitial fibrosis, tubular atrophy, and vascular intimal thickening)] between 3 and 12 months after the transplantation. Recently, in the DeKAF study, a lower Tac exposure after month 3 was also associated with an increased risk of acute rejection . The association between the Tac IPV and poor kidney transplantation outcome was not significantly modified within four patients subgroups based on their mean Tac C 0 .…”
Section: Discussionmentioning
confidence: 89%
“…While our results do not match exactly with those reported by others, for example, Israni et al . reported a significant interaction effect of TAC level with time since transplant, and Richards et al . .…”
Section: Discussionmentioning
confidence: 96%
“…below the initial target TAC trough level of 8–11 ng/ml). Another recent study of 1930 patients found a significant association between lower TAC trough levels (on a continuous scale) and a significantly higher AR rate during the first 6 months post‐transplant in a Cox multivariable model, with an even stronger relationship found during 3–6 months vs. 0–3 months post‐transplant (i.e. interaction effect of TAC trough level with time post‐transplant).…”
Section: Introductionmentioning
confidence: 95%
“…Tacrolimus has a narrow therapeutic window with high inter‐patient pharmacokinetic variability, requiring close monitoring of blood trough concentrations (initial goal 8‐12 ng/mL) and frequent early dose adjustments to reduce the risk of poor outcomes. Concentrations above the therapeutic range are associated with adverse effects such as nephrotoxicity, while sub‐therapeutic concentrations may increase the risk of acute rejection (AR) and graft failure (GF) . Many factors have been identified contributing to TAC inter‐patient pharmacokinetic variability such as drug‐drug interactions, drug‐food interactions, changes in hepatic metabolism, and nonadherence …”
Section: Introductionmentioning
confidence: 99%
“…Concentrations above the therapeutic range are associated with adverse effects such as nephrotoxicity, while sub-therapeutic concentrations may increase the risk of acute rejection (AR) and graft failure (GF). 1 Many factors have been identified contributing to TAC inter-patient pharmacokinetic variability such as drug-drug interactions, drug-food interactions, changes in hepatic metabolism, and nonadherence. 2 Genetic factors are also well-known to account for TAC pharmacokinetics differences between patients and several single-nucleotide polymorphisms (SNPs) have been associated with TAC troughs, including CYP3A5*3, CYP3A5*6, CYP3A5*7, CYP3A4*22, and possibly POR*28.…”
Section: Introductionmentioning
confidence: 99%